Positive electrode active material, its manufacturing method and lithium secondary battery using the same

A silicon-based composite anode material coated with ceramic and conductive carbon stabilizes volume changes, improving cycle performance and efficiency by mitigating the destruction of the SEI film in lithium batteries.

JP7627366B2Active Publication Date: 2025-02-05SINO APPLIED TECH TAIWAN CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023573376
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-02-25
Filing Date
2022-05-26
Publication Date
2025-02-05
Estimated Expiration
2042-05-26

Smart Images

  • Figure 0007627366000001
    Figure 0007627366000001
  • Figure 0007627366000002
    Figure 0007627366000002
  • Figure 0007627366000003
    Figure 0007627366000003
Patent Text Reader

Abstract

Positive electrode active material, its manufacturing method, and lithium secondary battery using the same [Solution] A positive electrode active material for a secondary battery comprising a composite material including silicon particles, a ceramic material, and conductive carbon, in which the ceramic material is formed on at least a portion of the surface of the silicon particles, and the conductive carbon is formed on the ceramic material so as to cover the silicon particles and the ceramic material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode material and its manufacturing method, and in particular to a positive electrode active material, its manufacturing method and a lithium secondary battery based on the positive electrode active material. [Background technology]

[0002] Artificial graphite and natural graphite are currently commonly used as anode (also called negative electrode) materials in lithium batteries. Since the capacity of currently commercialized graphite anodes is close to the theoretical capacity (372 mAh / g), finding a material with a higher electrical capacity will be a key step in increasing the energy density of the battery in the next generation.

[0003] Silicon-based anodes will be the main direction for the next stage. Silicon has a high theoretical capacitance of 4200mAh / g, more than 10 times that of current graphite anode materials, and silicon reserves are abundant and low-cost, making it the most promising candidate for the anode material of next-generation lithium-ion batteries. Summary of the Invention [Problem to be solved by the invention]

[0004] However, due to the intercalation of silicon and lithium during charging and discharging, multiple crystalline phases with different ratios are formed, which causes a serious swelling effect, and the swelling rate during charging can reach 300% (the original graphite anode is only 16%). Furthermore, the volume shrinks during discharging, and the repeated volume change is prone to problems such as silicon particle breakage, material crushing, and pole piece falling off, which reduces the cycle performance.

[0005] In addition, the solid electrolyte interphase film (SEI) on the anode surface is easily destroyed during the expansion process and reformed during the discharge process, so the SEI film on the silicon surface is constantly destroyed and reconstructed, and finally the thickness of the SEI film increases continuously, resulting in an increase in the film thickness, which in turn leads to an increase in the interfacial impedance and consumption of active materials, resulting in a decrease in capacity fade and coulombic efficiency.

[0006] In addition, due to the characteristics of silicon materials, a significant volume effect occurs during the charging and discharging process, which reduces the cycle performance and initial coulombic efficiency of the battery, making it difficult to put the battery to practical use. [Means for solving the problem]

[0007] In order to solve such problems, the present invention has the following configuration: That is, the positive electrode active material for a secondary battery is characterized in that the positive electrode active material for a secondary battery comprises a composite material containing silicon particles, a ceramic material, and conductive carbon, the ceramic material being formed on at least a partial area of ​​the surface of the silicon particles, and the conductive carbon being formed on the ceramic material so as to cover the silicon particles and the ceramic material.

[0008] The ceramic material also includes silicon carbide. It's okay to .

[0009] The ceramic material also includes a compound made of silicon, aluminum, oxygen, and nitrogen. It's okay to .

[0010] The chemical formula of the ceramic material is MxSi12-(m+n)Al(m+n)OnN16-n, where M is any one of the elements or compounds of yttrium (Y), zirconium (Zr), rhodium (Rh), palladium (Pd), lithium (Li), magnesium (Mg), calcium (Ca), barium (Ba), cerium (Ce), neodymium (Nd), europium (Eu), and ytterbium (Yb), and where x=0.01-0.5, m=0.1-2, and n=0.1-3. It is okay .

[0011] The composite material is in powder form, and the secondary particle diameter is between 1 and 500 μm. It is okay .

[0012] The primary particle diameter of the composite material is 5 nm or more and 1000 nm or less. It is okay .

[0013] The silicon particles include at least one of spherical units and linear units. It's okay to .

[0014] The diameter of the spherical units is between 5 nm and 1000 nm, and the diameter of the linear units is between 2 nm and 40 nm. It is okay .

[0015] The thickness of the ceramic material is between 0.1 nm and 3 nm. It is okay .

[0016] The thickness of the conductive carbon is between 3 nm and 10 nm. It is okay .

[0017] Also, a lithium secondary battery comprising a cathode, a diaphragm, and an anode, the cathode and the anode being disposed on either side of the diaphragm, the anode including an anode active material, and the anode active material including a composite material composed of silicon particles, a ceramic material, and conductive carbon.

[0018] The weight percentage of the positive electrode active material in the positive electrode is at least 70%. It is okay .

[0019] Also, a method for producing an anode active material, comprising: adding an organic solvent to a reaction chamber; providing a plurality of electrodes within the reaction chamber; disposing a silicon material in the reaction chamber and contacting the organic solvent; and applying a voltage to the plurality of electrodes to produce a composite material comprising silicon particles, a ceramic material, and conductive carbon.

[0020] The organic solvent may contain an alcohol compound. It may be included .

[0021] The organic solvent further contains an aluminum compound. It may be included .

[0022] The organic solvent further contains a flux. It may be included .

[0023] The composition of the flux contains any one of the elements or compounds of yttrium, zirconium, rhodium, palladium, lithium, magnesium, calcium, barium, cerium, neodymium, europium, and ytterbium. It may be included .

[0024] In addition, the composite material is subjected to a filtering process, and the filtered composite material is subjected to a heat treatment. It is okay .

[0025] The heat treatment includes a step of heating the composite material at a heating temperature of 900°C to 1500°C in an inert environment to produce the composite material in powder form. It may be included .

[0026] The heating temperature is 1200°C to 1500°C. It is okay . Effect of the Invention

[0027] According to the present invention, a secondary battery positive electrode active material is provided that includes a composite material including silicon particles, a ceramic material, and conductive carbon, and therefore is less likely to cause a significant volume effect during charging and discharging processes, thereby making it possible to provide a secondary battery positive electrode active material that can suppress a decrease in the cycle performance and initial coulombic efficiency of the battery. [Brief description of the drawings]

[0028] [Figure 1] 1 is a schematic diagram of a lithium secondary battery according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram of the composition of an anode material layer according to an embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic diagram of a cross-sectional structure of a positive electrode active material according to an embodiment of the present invention. [Figure 4] 1 is a flow chart of a method for manufacturing a positive electrode active material illustrating an embodiment of the present invention. [Diagram 5] 1 is a flow chart of a method for manufacturing a positive electrode active material illustrating an embodiment of the present invention. [Figure 6] 1 is a table showing experimental examples and comparative examples of the present invention, and showing specific experimental data relating to battery performance. [Figure 7] 7 is a transmission electron microscope photograph of the positive electrode active material prepared based on Experimental Example 1 of FIG. 6. [Figure 8] 7 is a transmission electron microscope photograph of the positive electrode active material prepared based on Experimental Example 1 of FIG. 6. [Figure 9] FIG. 7 is a diagram showing the results of X-ray diffraction analysis of the positive electrode active material prepared based on Experimental Example 2 of FIG. 6. [Figure 10]FIG. 7 is a scanning electron microscope image of the positive electrode active material produced in Experimental Example 2 of FIG. 6. [Figure 11] FIG. 7 is a diagram showing the results of X-ray diffraction analysis of a positive electrode active material prepared based on Experimental Example 7 of FIG. 6. [Figure 12] 7 is a scanning electron microscope photograph of the positive electrode active material prepared according to Experimental Example 11 of FIG. 6. [Figure 13] 7 is a scanning electron microscope photograph of the positive electrode active material prepared according to Experimental Example 11 of FIG. 6. [Figure 14] 7 is a scanning electron microscope photograph of the positive electrode active material prepared according to Experimental Example 12 of FIG. 6. [Figure 15] 7 is a scanning electron microscope photograph of the positive electrode active material prepared according to Experimental Example 12 of FIG. 6. [Figure 16] 1 is an experimental example of the present invention, and is a table showing specific experimental data relating to expansion characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] In order to more clearly describe the embodiments of the present application or the technical solutions of the prior art, the embodiments or the prior art will be described with reference to the necessary drawings. Note that these are only some of the embodiments of the present application, and those skilled in the art may obtain the embodiments of other drawings based on these drawings without creative efforts, but the simple modifications and additions to the present invention made by a third party shall be within the technical scope of the present invention.

[0030] In order to make the features and advantages of the present invention more easily understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. Also, the following description includes specific information related to the exemplary embodiments of the present invention. Furthermore, the drawings and the related detailed description of the present disclosure are for illustrative purposes only, and the technical scope of the present invention is not limited to such exemplary embodiments.

[0031] In addition, a person skilled in the art may conceive of other embodiments in which the present invention is modified or added, and such embodiments are also included in the technical scope of the present invention as long as they do not deviate from the spirit of the present invention. In addition, unless otherwise specified, the same or corresponding components in the drawings may be indicated by the same or corresponding reference numbers. Furthermore, the drawings, etc. in this disclosure are not necessarily drawn according to actual size, and may be enlarged or omitted as necessary.

[0032] In addition, for the sake of consistency and ease of understanding, the same components are labeled with the same reference numerals in the exemplary drawings. However, some exceptions may exist. Also, the features shown in different embodiments may differ in some respects. Therefore, the scope of the claims should not be narrowly limited to the technical features shown in the drawings.

[0033] The terms "first," "second," and "third" in the description of the present invention and the above figures are used to distinguish one object, region, level, or step from another, but are not used to describe a particular order, unless specifically used to indicate an order in the claims. Furthermore, the verb "comprise" and its variants are used in a non-exclusive sense, meaning that other elements may be included.

[0034] Furthermore, the phrases "consisting of" or "made up of" should be interpreted as exclusive. In other words, if an additional component or material is added to the inventive features of the present invention, it is not considered to fall within the technical scope of the present invention when it is expressed as "consisting of."

[0035] It should be noted that those skilled in the art should understand that during the actual detection process, any material or contaminant may be mixed in or a trace amount of impurities may be doped under unexpected circumstances. Even if a trace amount of impurities is mixed in, it does not affect the material, characteristics, or structure defined in the present invention, and does not constitute the addition of another material to the inventive features of the present invention.

[0036] The terms "connection" or "coupling" used in the present invention are not intended to mean that no spacer can exist between objects. In other words, "connecting or coupling two objects to each other" includes cases where the two objects are directly connected or coupled to each other, but also includes, in principle, a state where the objects are connected or coupled to each other via another object equivalent to a spacer.

[0037] In all descriptions of specific numerical values ​​in the present invention, although not directly stated, they all include the meaning of "approximately" or "substantially". In other words, these specific values ​​cover a possible range of numerical error to reflect unintended effects or unforeseen circumstances that may occur during the selection of a process or material. Here, the range of numerical error includes numerical changes that do not significantly change the structure, properties, or effects of the material. For example, the range of numerical error is about 0% to 10%, and this range of numerical error is recognized as something that can naturally occur to those skilled in the art.

[0038] In the present invention, spatial positional relationships such as "above", "below", "from above", "from below", "to the left side of...", and "to the right side of..." are all merely illustrative. Note that the relative positional relationships shown in the drawings do not limit the actual arrangement of structures.

[0039] In the present invention, the terms anode and negative electrode are interchangeable terms, and the terms cathode and positive electrode are interchangeable terms.

[0040] Fig. 1 is a cross-sectional view of a lithium secondary battery according to an embodiment of the present invention. Referring to Fig. 1, a lithium secondary battery 10 of this embodiment includes a cathode 11, a diaphragm 12, and an anode 13. Here, the cathode 11 includes a cathode material layer 110 and a cathode current collector 111, and the anode 13 includes an anode material layer 130 and an anode current collector 131.

[0041] The cathode 11 and the anode 13 are disposed on either side of the diaphragm 12. More specifically, the cathode material layer 110 is disposed between the cathode current collector 111 and the diaphragm 12 (disposed above the diaphragm 12 in FIG. 1), and the anode material layer 130 is disposed between the anode current collector 131 and the diaphragm 12 (disposed below the diaphragm 12 in the drawing).

[0042] When the lithium secondary battery 10 is charged, lithium ions invade from the cathode material layer 110, pass through the electrolyte via the diaphragm 12, and enter the anode material layer 130. Conversely, when the lithium secondary battery 10 is discharged, lithium ions invade from the anode material layer 130, pass through the electrolyte via the diaphragm 12, and are inserted into the cathode material layer 110, and electrons are output from the cathode current collector 111 due to valence balance.

[0043] In this embodiment, the cathode material layer 110 can be formed based on any possible cathode active material, but the present invention is not limited thereto. The anode material layer 130 is mainly formed based on one or more anode active materials, at least one of which is realized by using a composite material based on nanosilicon particles.

[0044] The composite material based on nano silicon particles is used as the positive electrode active material in the lithium secondary battery 10, which can solve the volume effect of silicon in the charge / discharge process, provide better charge / discharge performance and capacity, and at the same time provide excellent anti-oxidation properties.

[0045] The composition of the anode material layer 130 and the specific structure of the composite material are further described below with reference to Figures 2 and 3. Figure 2 is a schematic diagram of the composition of the anode material layer in an embodiment of the present invention. Also, Figure 3 is a schematic cross-sectional structure diagram of the anode active material in an embodiment of the present invention.

[0046] 2 and 3, the anode material layer 130 according to the embodiment of the present invention has an anode active material M1. Here, the anode active material M1 is realized by a composite material 200 as shown in FIG. 3. In detail, the composite material 200 includes silicon particles 210, a ceramic material 220, and conductive carbon 230. The ceramic material 220 is formed on at least a portion of the surface of the silicon particles 210, and the conductive carbon 230 is formed on the ceramic material 220 so as to cover the silicon particles 210 and the ceramic material 220.

[0047] In other words, the ceramic material 220 in the composite material 200 is formed between the silicon particles 210 and the conductive carbon 230, forming a three-layer structure in sequence (i.e., from the inside to the outside, the arrangement is silicon particles 210, ceramic material 220, and conductive carbon 230).

[0048] From another perspective, the ceramic material 220 and the conductive carbon 230 attached thereto can be considered as one entity, and the silicon particles 210 can be considered to be covered with a layer of ceramic material containing conductive carbon, and can be considered to be a two-layer structure (i.e., from the inside to the outside, the ceramic material includes the silicon particles 210 and a carbon layer).

[0049] The size of the silicon particles 210 in the composite material 200 is at the nanometer level, which can be obtained by heating the silicon material to a plasma state (i.e., plasma state). The silicon material can be, for example, a pure silicon wafer, an N-type silicon wafer, or a P-type silicon wafer, but the present invention is not limited thereto.

[0050] The silicon particles 210 may have a particle size of, for example, 2 nm to 1000 nm. The particular size range may be adjusted by modifying process parameters. For example, in some embodiments, the silicon particles may have a particle size of less than 150 nm, thereby reducing the volume effect during charging and discharging.

[0051] Furthermore, according to different process conditions, the silicon particles 210 can be spherical or linear units. The diameter of the spherical units is 5 nm to 1000 nm. The diameter of the linear units is 2 nm to 40 nm. Regardless of whether the silicon particles 210 are spherical or linear, the radial cross-section of the composite material 200 has a three-layer structure similar to that shown in FIG. 3.

[0052] The ceramic material 220 in the composite material 200 may be, for example, silicon carbide (SiC) or a compound synthesized from silicon, aluminum, oxygen and nitrogen, such as a sialon (SiAlON) ceramic.

[0053] The ceramic material 220 is formed on the surface of the silicon particles 210, and has a thickness of, for example, 0.1 to 3 nm. When plasma processing is performed, the ceramic material 220 is a silicon material and is generated after an organic solvent (hereinafter the same as "solvent") in a reaction chamber is heated. By forming the ceramic material 220 on the silicon particles 210, it is possible to reduce the expansion of the anode when the lithium secondary battery is repeatedly charged and discharged.

[0054] In this embodiment, where the ceramic material 220 is silicon carbide, the thickness of the bond may be, for example, 0.1 to 0.5 nm. In this embodiment, the silicon carbide attached to the silicon particles 210 can be obtained by adding an organic solvent containing an alcohol compound when the silicon material is plasma-treated. The manufacturing method will be specifically described in the following examples.

[0055] In one embodiment where ceramic material 220 is a sialon ceramic, ceramic material 220 may be α-sialon, β-sialon, or O-sialon. The chemical formulas of B-sialon and O-sialon are Si(6-z)AlzOzN(8-z) and Si(2-z)AlzO(1+z)N(2-z), respectively. Additionally, the range of z values ​​in the chemical formulas of β-sialon and O-sialon is as follows: z=0 to 4.2.

[0056] The chemical formula of α-sialon is, for example, MxSi12-(m+n)Al(m+n)OnN16-n, where M is any of the following elements or compounds:

[0057] Transition elements: Yttrium (Y), Zirconium (Zr), Rhodium (Rh), Palladium (Pd). Alkaline metal elements: Lithium (Li). Alkaline earth elements: Magnesium (Mg), Calcium (Ca), Barium (Ba). Lanthanides: Cerium (Ce), Neodymium (Nd), Europium (Eu), Ytterbium (Yb).

[0058] The numerical ranges of x, m, and n in the chemical formula of α-sialon are x=0.01 to 0.5, m=0.1 to 2, and n=0.1 to 3. In this embodiment, the sialon ceramic attached to the silicon particles 210 can be obtained by adding an organic solvent containing an alcohol compound and an aluminum compound during the plasma treatment of the silicon material. The manufacturing method will be specifically described in the following examples.

[0059] In the above embodiment, whether the ceramic material 220 is silicon carbide or sialon ceramic, the expansion rate can be effectively suppressed compared to existing positive electrode active materials. Here, sialon ceramic has high hardness, high toughness, low thermal expansion coefficient and excellent thermal shock resistance, so that the expansion rate can be further suppressed compared to silicon carbide.

[0060] Based on different process conditions, the conductive carbon 230 in the composite material 200 can exist in different structures, such as graphene, carbon nanotube, or conductive carbon black, and can be attached to the ceramic material 220. Examples include, but are not limited to, superconducting carbon black (super-P), acetylene black, Ket jenblack, channel black, furnace black, lamp black, thermal black, nanohorn, or vapor-deposited carbon.

[0061] In this embodiment, the thickness of the conductive carbon 230 is between 3 and 10 nm. By forming the conductive carbon 230 on the ceramic material 220, oxidation of the silicon particles 210 can be further suppressed or prevented.

[0062] The above is a description of the layer structure of the minimum unit particles (i.e., primary particles) of the composite material 200. It can be seen that the particle size of the minimum unit particles of the composite material 200 is approximately 5 nm to 1000 nm. In this embodiment, the silicon particles 210 constitute at least 1 weight percent of the composite material 200. This refers to the weight percentage of the silicon particles 210 in the corresponding minimum unit particles.

[0063] Here, the silicon particles 210 are shown as being completely covered by the ceramic material 220, which in turn is completely covered by the conductive carbon 230. However, during the actual material preparation process, there may be defects in the formation of the individual material crystals, resulting in the silicon particles 210 and the ceramic material 220 being only partially covered by the outer layer material.

[0064] For example, some areas of the silicon particles 210 may be covered or exposed only by the conductive carbon 230, and some areas of the ceramic material 220 may be exposed.

[0065] In other words, the structure of the composite material 200 defined in the present invention is not limited to the inner layer material being completely covered by the outer layer material. It is sufficient to confirm that at least a part of the surface area of ​​the silicon particle 210 is covered by the ceramic material 220, and the ceramic material in this part is further covered with the conductive carbon 230. In other words, the ceramic material 220 is formed on at least a part of the surface of the silicon particle 210, and the conductive carbon 230 is formed on the ceramic material 220 so as to cover the silicon particle 210 and the ceramic material 220, and such a structure is also included in the scope of the structure of the composite material 200 defined in the present invention.

[0066] In this embodiment, the final form of the manufactured composite material 200 may be in the form of a powder. That is, there is cohesion between the minimum unit particles of the composite material 200, and a plurality of the minimum unit particles are cohered to form aggregates, and the aggregates are powder particles.

[0067] The particle size of the powder particles (or the particle size of the aggregates) is 1 to 500 μm. More specifically, in this embodiment, the particle size of the positive electrode active material M1 / composite material 200 is the primary particle size (primary particle The particle size of the smallest unit particle is the primary particle size (5 nm to 1000 nm) of the positive electrode active material M1 / composite material 200, and the particle size of the powder particle / aggregate is the secondary particle size (1 to 500 μm) of the positive electrode active material M1 / composite material 200.

[0068] In this embodiment, the final form of the obtained composite material 200 may be suspended in a solution. That is, there is no sufficient cohesive force between the individual minimum unit particles in the composite material for a plurality of minimum unit particles to aggregate and form aggregates. Therefore, the particle size of the positive electrode active material M1 / composite material 200 refers to the primary particle size (5 nm to 1000 nm).

[0069] In this embodiment, the anode material layer 130 further comprises a conductive material M2. The conductive material M2 can be any material that is conductive and does not cause chemical changes in the battery. For example, the conductive material M2 can be a conductive material such as graphite (including artificial graphite and natural graphite), conductive carbon black, conductive fibers, conductive metal oxides, and polyphenyl derivatives.

[0070] In this embodiment, the anode material layer 130 may further include a binder M3 for improving the bonding strength between the diaphragm 12 and the anode current collector 131. In this embodiment, the anode material layer 130 may further include a filler.

[0071] In this embodiment, the anode 1 of 3 The weight percentage of the positive electrode active material M1 is about 70-80% by weight, and the positive electrode 1 of 3 The weight percentage of the conductive material M2 is about 10 to 20%. of 3 The weight percentage of adhesive M3 is about 0 to 10%.

[0072] Specifically, the electrical conductivity of the silicon material is increased by nano-sizing the silicon material and coating it with the ceramic material 220 and the conductive carbon 230. Through the nano-sizing process, the particle size is reduced, which is beneficial to the release of stress and weakens the volume effect.

[0073] Therefore, when the nanosilicon-based composite material 200 is used as the positive electrode active material M1 of the lithium secondary battery 10, the positive electrode 13 still expands during the charging and discharging process, but is not easily broken, so that the repeated cycle performance can be improved. At the same time, the silicon material can be doped with III-V group elements to reduce the resistance of the original silicon material and increase the conductivity of the material.

[0074] Furthermore, since silicon material is a semiconductor, the conductivity of silicon particles 210 can be improved by coating with conductive carbon 230 in various ways, such as coating with graphene, carbon nanotubes, nanohorns, etc. It also improves the rate performance and prevents the silicon particles 210 from agglomerating, and the complete conductive carbon 230 coating reduces the direct contact between the silicon material and the electrolyte, inhibits the excessive growth of the SEI film, stabilizes the interface, and improves the Coulombic efficiency.

[0075] Meanwhile, through the control of the process conditions, the silicon particles 210 in the composite material 200 can form one-dimensional nanosilicon wires (i.e., linear units). The nanosilicon wires expand in the axial direction (along the direction of the nanosilicon wires), so that the stress can be fully released without causing cracks or damage to the nanosilicon wires. Therefore, the expansion effect is effectively reduced and the powdering of the electrode is prevented. Also, the anode material layer 130 can be prevented from peeling off from the surface, which can prevent the battery from failing, thereby extending the cycle life of the battery.

[0076] 4 and 5 are flow charts of a method for manufacturing anode active material according to an embodiment of the present invention. First, referring to FIG. 4, in this embodiment, the method for manufacturing anode active material includes the following steps: Add an organic solvent into a reaction chamber in which a plurality of electrodes are provided (step S110). Place a silicon material in the reaction chamber to contact with the organic solvent (step S120). Apply a voltage to the plurality of electrodes to generate a composite material (e.g., 230) including silicon particles (e.g., 210), a ceramic material (e.g., 220), and conductive carbon (step S130).

[0077] In step S110, the structure of the positive electrode active material is generated according to the purpose, and the organic solvent added to the reaction chamber may be an alcohol compound solvent (methanol, ethanol, isopropyl alcohol IPA, etc.), a mixed organic solvent containing an alcohol compound and an aluminum compound, or a mixed organic solvent containing an alcohol compound, an aluminum compound, and a flux. Examples of the aluminum compound include aluminum chloride, aluminum sulfate, and aluminum nitrate.

[0078] In this embodiment, the composition of the flux includes any of the following elements or compounds thereof: yttrium, zirconium, rhodium, palladium, lithium, magnesium, calcium, barium, cerium, neodymium, europium, and ytterbium, where, for example, the flux may be yttrium nitrate, barium nitrate, lithium hydroxide, etc.

[0079] Additionally, the organic solvent may contain dispersants, surfactants, compounds of group III and group V elements, conductive carbon or carbon precursors.

[0080] The dispersant, for example, polyvinylpyrrolidone (PVP), can be used to prevent aggregation and precipitation of the nanosilicon composite material produced. In this embodiment, the weight percent concentration of PVP in the organic solvent ranges from 0.01 to 1%. In this embodiment, when the weight percent concentration of PVP in the organic solvent is 0.01 to 0.7%, a better effect is achieved.

[0081] The compound of group III and group V elements may include boric acid, phosphoric acid, etc. In this embodiment, the weight percent concentration of the compound of group III and group V elements in the organic solvent is between 0.001% and 5%. By adding the compound of group III and group V elements, the anode nanosilicon ion can be modified during the reaction process to reduce the material resistance, thereby increasing the capacity of the lithium secondary battery.

[0082] The conductive carbon material may be the same as the conductive carbon 230 described above. The carbon precursor may be introduced into the reaction chamber in a gaseous state to be mixed with an organic solvent. Among them, the carbon precursor gas can further control the formation pattern of the carbon layer. Carbon coatings with high specific surface areas, such as graphene and carbon nanotubes, form a composite of ultra-high conductive carbon, a thin layer of silicon carbide, and silicon materials.

[0083] In step S120, the silicon material used to prepare the anode active material may be a pure silicon wafer, an N-type silicon wafer, or a P-type silicon wafer. If the pure silicon wafer is selected as the silicon material, in addition to the alcohol compound, at least additional group III and group V element compounds are added to the organic solvent in step S110. If the N-type or P-type silicon wafer is selected as the silicon material, the doping amount of group III and group V elements can be selected between 0.001 and 2 weight percent.

[0084] In this embodiment, the silicon material disposed in the reaction chamber can be processed into a plurality of silicon units having a strip structure, such as, for example, a chain (wire) or rod-shaped material containing inorganic matter, the inorganic matter including one or more of silicon, silicon powder, mixed powder of silicon and other metals, silicon inorganic mixture, silicon alloy, silicon wafer, and silicon engineering waste slurry, but the present invention is not limited thereto.

[0085] In an embodiment using a pure silicon wafer not doped with group III and group V elements as the silicon material, the resistance value of the processed silicon unit (or silicon rod) is 5000 to 10000 ohms. In an embodiment using an N-type or P-type silicon wafer as the silicon material, the resistance value of the silicon unit is in the range of 0.1 to 20 ohms.

[0086] In step S130, a voltage is applied to the electrodes, for example, 5 kV to 20 kV, and the electrodes respond to the applied voltage to heat the silicon material in the reaction chamber to perform plasma treatment. During the plasma treatment to form the nanosilicon particles, the nanosilicon particles react with the organic solvent to form a ceramic material and a conductive carbon layer on the silicon particles.

[0087] The particular type of ceramic material that is produced on the silicon particles during reaction with the organic solvent depends on the composition of the organic solvent.

[0088] For example, if the organic solvent contains only alcohol compounds, when a voltage is applied to the electrodes, the silicon material reacts with the organic solvent to form silicon carbide as a ceramic material. If the organic solvent is a mixed organic solvent containing alcohol compounds and aluminum compounds, when a voltage is applied to the electrodes, the silicon material reacts with the organic solvent to form a sialon ceramic based on silicon, aluminum, oxygen, and nitrogen.

[0089] From a manufacturing process perspective, the produced anode active material can be considered to include silicon particles formed by heating a silicon material to a plasma state. The silicon material is placed in a reaction chamber filled with an organic solvent and heated, which forms a ceramic material and conductive carbon composite layer on the silicon particles during the heating process.

[0090] More specifically, in the above steps S110 to S130, a voltage of 5 kV to 20 kV is applied to the silicon material via the electrodes and the organic solvent in the reaction chamber.

[0091] More specifically, after the capacitor of the high voltage charger is charged, the connected electrode switch is also discharged at the same time, the silicon material is heated and becomes a plasma state, the resistivity increases due to the temperature rise of the silicon material, energy consumption is concentrated in the silicon material part, and finally nano silicon particles are formed. At the same time, plasma is instantaneously generated, and the heat-resistant ceramic material is vaporized, condensed and bonded to form a conductive carbon layer.

[0092] The above-mentioned manufacturing method for the preparation of the positive electrode active material provides a uniform powdered composite material, and the operation is simple. In addition, since no chemicals are used except for organic solvents, silicone, and dispersants, almost no by-products or wastes are generated.

[0093] In addition, because this manufacturing method can complete the plasma formation, vaporization, and extinction process within tens of microseconds, even with the initial high voltage and momentary large current, the actual energy input is 2 to 5 times the energy required to gasify silicon, significantly reducing the energy consumption for particle generation and enabling mass production at low cost.

[0094] Furthermore, since the particles of nanosilicon composite material produced by this manufacturing method are dispersed in an organic solvent during production, they are easy to use and are unlikely to be released into the atmosphere and cause pollution, making them environmentally clean and a safe manufacturing method for humans, and unlikely to harm the environment or human body.

[0095] An example of a detailed process flow of the method for preparing the positive electrode active material will be further described with reference to Fig. 5. Referring to Fig. 5, the method for preparing the positive electrode active material in this embodiment includes the following steps: Add an organic solvent to a reaction chamber (step S210).

[0096] The silicon material is processed into a plurality of silicon units having a strip structure (step S220). The silicon units are placed in a reaction chamber to contact with an organic solvent (step S230). A voltage is applied to the electrodes in the reaction chamber to generate a composite material in the solution (step S240). The composite material is filtered (step S250). The filtered composite material is dried (step S260). The dried composite material is subjected to a heat treatment to generate a final powder composite material (step S270).

[0097] Specifically, through steps S210 to S240, a composite material is basically produced, but is still mixed in the solution. Through the subsequent steps S250 to S270, the composite material is further separated as a positive electrode active material.

[0098] In this embodiment, step S250 may further include a step of passing the composite material through a screening device to filter the solution mixed with the composite material (step S252), and a step of centrifuging the composite material that has passed through the screening device. Next, a composite material in a slurry state is prepared (step S254). Here, the screening device may be, for example, a steel mesh, but the present invention is not limited thereto.

[0099] After the centrifugation step, in step S260 of the drying step, the slurried composite material can be vacuum-dried at a first temperature, which may be, for example, between 50°C and 100°C.

[0100] Next, in a heat treatment step S270, the vacuum dried mud is heated in an inert environment at a second temperature, for example between 900°C and 1500°C.

[0101] In this embodiment, the heating time in step S270 may be between 2 hours and 5 hours. After the heat treatment, the powder composite material can be separated, and the particle size of the composite powder (i.e., the secondary particle size of the composite material) is 1-500 μm.

[0102] In addition, the nanosilicon particles can form a spherical structure or a linear structure depending on the heating temperature. In this embodiment, when the second temperature is 900°C to 1200°C, the silicon particles form a spherical unit, and when the second temperature is 1200°C to 1500°C, the silicon particles form a linear unit.

[0103] Here, it should be noted that depending on the selection of the second temperature, not all of the silicon material is generated into spherical units or linear units during the formation process of the nanosilicon particles. If the selected temperature is between the two temperature ranges, the silicon material may generate multiple spherical units and multiple linear units. That is, the produced silicon particles can simultaneously contain the structure of nanosilica powder and nanosilicon wire.

[0104] In this embodiment, the drying step S260 may be omitted, that is, the heating step S270 may be directly performed after the filtering step S250 of the solution containing the composite material.

[0105] Figure 6 shows specific experimental data on the battery performance of several experimental examples and comparative examples of the present invention. Referring to Figure 6, two groups of comparative examples (Comparative Example 1 and Comparative Example 2) and 12 groups of experimental examples (Experimental Example 1 to Experimental Example 12) are shown to show the accuracy of the preparation method of the positive electrode active material shown by the present invention. The composite structure can be obtained by the above-mentioned method.

[0106] In addition, based on the experimentally obtained characteristics of lithium secondary batteries made from the composite material, it was confirmed that the composite material / anode active material proposed in the present invention has superior performance to existing anode active materials based on silicon materials.

[0107] Specifically, Comparative Example 1 is a coin-type battery made of a silicon-carbon anode active material (model number: KSC-1265) manufactured by Shin-Etsu Chemical Co., Ltd., in which the silicon is not the nanosilicon composite material proposed in the present invention. Comparative Example 2 is a coin-type battery made of a nanosilicon material not doped with group III and group V elements.

[0108] On the other hand, Experimental Examples 1 to 5 are experimental configurations in which silicon carbide was produced as the ceramic material. Experimental Examples 6 to 12 are experimental configurations in which sialon ceramic was produced as the ceramic material. The experimental conditions for Experimental Examples 6 to 10 were set to produce nanosilica powder, and the heat treatment temperature was set to 900 to 1200°C. The experimental conditions for Experimental Examples 11 and 12 were set to produce nanosilicon wires, that is, the heat treatment temperature was set to 1200 to 1500°C.

[0109] In Experimental Example 1, the organic solvent in the plasma reaction chamber contains methanol, and a pair of stainless steel electrodes are installed. An N-type silicon wafer is cut into a grid shape with a thickness of 0.8 mm, a width of 1 mm, and a length of 100 mm, and a silicon rod with a resistance of 2 Ω is fabricated, into which methane is introduced. The chamber is used as a coating gas carbon source.

[0110] The nanosilicon composite is produced using a capacitor charged at 11 kV. The nanosilicon composite carbon layer composite is filtered through a steel mesh and centrifuged at 11000 rpm to obtain nanosilicon particle slurry.

[0111] This slurry is subjected to high-temperature heat treatment at 1100°C for 2 hours in an argon atmosphere, and then decomposed, dispersed, and classified to produce nanosilicon composite nanoparticle powder.

[0112] The nanosilicon composite material contains more than 5 weight percent of nanosilica powder, and the anode is made of 10 weight percent of superconducting carbon black (super P) conductive material and 10 weight percent of polyvinylidene fluoride (PVDF) adhesive, with the anode active material after mixing artificial graphite making up 80% of the total weight of the anode. A coin-type battery with a diameter of 20 mm and a height of 3.2 mm was manufactured using the nanosilicon composite powder as the anode active material.

[0113] As shown in FIGS. 7 and 8, FIGS. 7 and 8 are transmission electron microscope (TEM) images of the positive electrode active material prepared based on Experimental Example 1 of FIG. 6. From the TEM image of the sample (electrode plate sample to be the negative electrode of the battery) obtained in Experimental Example 1, it can be observed that a uniform graphene coating is formed through this process, and the thickness of the graphene coating is about 3 to 5 nm.

[0114] In Experiment 2, the organic solvent in the plasma reaction chamber contained isopropyl alcohol (IPA) and carbon nanotubes, and a pair of stainless steel electrodes were installed. A P-type silicon wafer was cut into a grid shape with a thickness of 0.8 mm, a width of 1 mm, and a length of 100 mm to produce silicon rods. The resistance of the P-type silicon rod was 1 ohm. A capacitor charged with a voltage of 11 kV was used to produce nanosilicon composites, and the carbon layer composite of the nanosilicon composite was filtered through a steel mesh and centrifuged at 11,000 rpm to obtain nanosilicon particle slurry.

[0115] This slurry is subjected to high-temperature heat treatment at 1100°C for 2 hours in an argon atmosphere, and then decomposed, dispersed, and classified to produce nanosilicon composite nanoparticle powder.

[0116] The nanosilicon composite material contains more than 5 weight percent of nanosilica powder, and the anode after mixing with artificial graphite is composed of 80 weight percent of the total weight of the anode as the anode active material, 10 weight percent of super P conductive material, and 10 weight percent of PVDF adhesive. A coin-type battery with a diameter of 20 mm and a height of 3.2 mm was manufactured using the nanosilicon composite powder as the anode active material.

[0117] As shown in FIG. 9, FIG. 9 shows the results of X-ray diffraction analysis (XRD) of the anode active material manufactured based on Experimental Example 2 in FIG. 6. From the XRD analysis results of the powder (Modified-Si, M-Si) of Experimental Example 2 compared with pure Si (Baseline-Si, B-Si), it can be confirmed that silicon carbide compounds are generated during the manufacturing process.

[0118] Also, as shown in FIG. 10, FIG. 10 is a scanning electron microscope (SEM) image of the positive electrode active material manufactured based on Experimental Example 2 of FIG. 6. From the SEM image of the sample (electrode plate sample that will become the negative electrode of the battery) obtained in Experimental Example 2, it can be seen that uniform carbon nanotubes are formed through this process, are coated between silicon particles, and have good dispersibility.

[0119] In experimental example 3, the organic solvent in the plasma reaction chamber contains ethanol and aluminum chloride, the solid content of aluminum chloride in the solvent is 0.01%, and a pair of stainless steel electrodes is installed. The P-type silicon wafer is cut into a grid shape with a thickness of 0.8 mm, a width of 1 mm, and a length of 100 mm to prepare silicon rods. The resistance of the P-type silicon rod is 1 ohm. A capacitor charged with a voltage of 11 kV is used to prepare nanosilicon composite material, and the carbon layer composite of the nanosilicon composite material is filtered through a steel mesh and centrifuged at 11000 rpm to obtain nanosilicon particle slurry.

[0120] This slurry is subjected to high-temperature heat treatment at 1100°C for 5 hours in an argon atmosphere, after which it is decomposed, dispersed, and classified to produce nanoparticle powder of nanosilicon composite material.

[0121] The nanosilicon composite material contains more than 5 weight percent of nanosilica powder, and the anode after mixing with artificial graphite is made up of 80% of the total weight of the anode as anode active material, 10 weight percent of super P conductive material, and 10 weight percent of PVDF. A coin-type battery with a diameter of 20 mm and a height of 3.2 mm was manufactured using the nanosilicon composite powder as the anode active material.

[0122] In Experimental Example 4, the organic solvent in the plasma reaction chamber contains ethanol and gallium chloride, the solid content of gallium chloride in the solvent is 0.01%, and a pair of stainless steel electrodes is installed. The P-type silicon wafer is cut into a grid shape with a thickness of 0.8 mm, a width of 1 mm, and a length of 100 mm to prepare silicon rods. The resistance of the P-type silicon rod is 1 ohm. The nanosilicon composite material was fabricated using a capacitor charged at 11 kV. The nanosilicon-carbon layer composite was filtered through a steel mesh and centrifuged at 11,000 rpm to obtain nanosilicon particle slurry.

[0123] The mud was subjected to high-temperature heat treatment at 1100°C for 5 hours in an argon atmosphere, and then decomposed, dispersed, and classified to produce nanosilicon composite nanoparticle powder.

[0124] The nanosilicon composite material contains more than 5 weight percent nanosilica powder, and the anode after mixing with artificial graphite is made up of 80 weight percent anode active material, 10 weight percent super P conductive material, and 10 weight percent PVDF adhesive. A coin-type battery with a diameter of 20 mm and a height of 3.2 mm was manufactured using the nanosilicon composite powder as the anode active material.

[0125] In experimental example 5, the organic solvent in the plasma reaction chamber contains ethanol and phosphoric acid, the solid content of phosphoric acid in the solvent is 0.01%, and a pair of stainless steel electrodes is installed. The P-type silicon wafer is cut into a grid shape with a thickness of 0.8 mm, a width of 1 mm, and a length of 100 mm to prepare a silicon rod. The resistance value of the P-type silicon ingot is 1 Ω. The nanosilicon composite material is produced using a capacitor charged at 11 kV. The nanosilicon composite carbon layer composite is filtered through a steel mesh and centrifuged at 11,000 rpm to obtain a nanosilicon particle slurry.

[0126] High-temperature heat treatment of mud: Treat at 1100°C for 3 hours in an argon atmosphere, then decompose, disperse, and classify to produce nanosilicon composite nanoparticle powder.

[0127] The nanosilicon composite material contains more than 5 weight percent nanosilica powder, and the anode after mixing with artificial graphite has a positive electrode active material that accounts for 80% of the total weight of the anode, and is made of 10 weight percent Super P conductive material and 10 weight percent PVDF adhesive. A coin-type battery with a diameter of 20 mm and a height of 3.2 mm was manufactured using the nanosilicon composite powder as the positive electrode active material.

[0128] In Experiment 6, the organic solvent in the plasma reaction chamber contains ethanol and aluminum chloride. The solid content of aluminum chloride in the solvent is 0.01%, and a pair of stainless steel electrodes is attached. The N-type silicon wafer is cut into a grid shape with a thickness of 0.8 mm, a width of 1 mm, and a length of 100 mm to prepare silicon rods. The resistance value of the N-type silicon rods is 0.1 Ω.

[0129] The nanosilicon composite is produced using a capacitor charged at 11 kV. The nanosilicon composite carbon layer composite is filtered through a steel mesh and centrifuged at 11000 rpm to obtain a nanosilicon particle slurry.

[0130] This slurry is heat-treated at 1100°C for three hours under a nitrogen atmosphere, then decomposed, dispersed, and classified to produce nanoparticle powder of nanosilicon composite material.

[0131] The nanosilicon composite material contains more than 5 weight percent nanosilica powder, and the anode, after mixing with artificial graphite, is made of 80 weight percent anode active material, 10 weight percent super P conductive material, and 10 weight percent polyvinylidene fluoride (PVDF) adhesive. A coin-type battery with a diameter of 20 mm and a height of 3.2 mm was manufactured using the nanosilicon composite powder as the anode active material.

[0132] In Experiment 7, the organic solvent in the plasma reaction chamber includes ethanol, aluminum sulfate, and yttrium nitrate. The solid content of aluminum sulfate in the solvent is 0.01%, and the solid content of yttrium nitrate is 0.005%, and a pair of stainless steel electrodes is installed.

[0133] P-type silicon wafers are cut into intervals with a thickness of 0.8 mm, width of 1 mm, and length of 100 mm. They are fabricated as silicon rods, and the resistance of the P-type silicon rods is 1 ohm. Nanosilicon composites are fabricated using a capacitor charged at 11 kV. The carbon layer composite of nanosilicon composites is filtered through a steel mesh and centrifuged at 11000 rpm to obtain nanosilicon particle slurry.

[0134] This slurry is subjected to high-temperature heat treatment at 1100°C for 3 hours under a nitrogen atmosphere, and then decomposed, dispersed, and classified to produce nanosilicon composite nanoparticle powder.

[0135] The nanosilicon composite material contains more than 5 weight percent nanosilica powder, and the anode after mixing with artificial graphite is made up of 80 weight percent anode active material, 10 weight percent super P conductive material, and 10 weight percent PVDF adhesive. A coin-type battery with a diameter of 20 mm and a height of 3.2 mm was manufactured using the nanosilicon composite powder as the anode active material.

[0136] As shown in FIG. 11, FIG. 11 shows the XRD analysis result of the positive electrode active material manufactured based on Experimental Example 7 of FIG. 6. From the XRD analysis result of the powder (Modified-Si) of Experimental Example 7, it can be confirmed that a sialon ceramic (Sialon) compound is generated during the manufacturing process.

[0137] In Experimental Example 8, the organic solvent in the plasma reaction chamber contains ethanol and aluminum sulfate, the solid content of aluminum sulfate in the solvent is 0.01%, and a pair of stainless steel electrodes is installed. The P-type silicon wafer is cut into a grid shape with a thickness of 0.8 mm, a width of 1 mm, and a length of 100 mm to prepare silicon rods. The resistance of the P-type silicon rod is 1 ohm. The nanosilicon composite is fabricated using a capacitor charged at 11 kV. The carbon layer composite of the nanosilicon composite is filtered through a steel mesh and centrifuged at 11000 rpm to obtain nanosilicon particle slurry.

[0138] This slurry is subjected to high-temperature heat treatment at 1100°C for 3 hours under a nitrogen atmosphere, and then decomposed, dispersed, and classified to produce nanoparticle powder of nanosilicon composite material.

[0139] The nanosilicon composite material contains more than 5 weight percent nanosilica powder, and the anode active material after mixing with artificial graphite accounts for 80% of the total weight of the anode, and is made of 10 weight percent Super P conductive material and 10 weight percent PVDF adhesive. A coin-type battery with a diameter of 20 mm and a height of 3.2 mm was manufactured using the nanosilicon composite powder as the anode active material.

[0140] In Experimental Example 9, the organic solvent in the plasma reaction chamber contains ethanol and aluminum nitrate. The solid content of aluminum nitrate in the solvent is 0.01%, and a pair of stainless steel electrodes is attached. The P-type silicon wafer is cut into a grid shape with a thickness of 0.8 mm, a width of 1 mm, and a length of 100 mm to prepare silicon rods. The resistance of the P-type silicon rod is 1 ohm. The nanosilicon composite is fabricated using a capacitor charged at 11 kV. The carbon layer composite of the nanosilicon composite is filtered through a steel mesh and centrifuged at 11000 rpm to obtain nanosilicon particle slurry.

[0141] This slurry is subjected to high-temperature heat treatment at 1100°C for 3 hours under a nitrogen atmosphere, and then decomposed, dispersed, and classified to produce nanosilicon composite nanoparticle powder.

[0142] The nanosilicon composite material contains more than 5 weight percent nanosilica powder, and the anode is made by mixing the anode active material, which accounts for 80% of the total weight of the anode, with artificial graphite, 10 weight percent Super P conductive material, and 10 weight percent PVDF adhesive. A coin-type battery with a diameter of 20 mm and a height of 3.2 mm was manufactured using the nanosilicon composite powder as the anode active material.

[0143] In Experimental Example 10, the organic solvent in the plasma reaction chamber contains ethanol, aluminum chloride, and lithium hydroxide, and the solid content of aluminum chloride in the solvent is 0.01%, and the content of lithium hydroxide is 0.005%. Then, a pair of stainless steel electrodes is attached. The P-type silicon wafer is cut into a lattice shape with a thickness of 0.8 mm, a width of 1 mm, and a length of 100 mm to prepare a silicon rod. Here, the resistance value of the P-type silicon ingot is 1 Ω. The nanosilicon composite is fabricated using a capacitor charged at 11 kV. The carbon layer composite of the nanosilicon composite is filtered through a steel mesh and centrifuged at 11,000 rpm to obtain a nanosilicon particle slurry.

[0144] This slurry is subjected to high-temperature heat treatment at 1100°C for 3 hours under a nitrogen atmosphere, and then decomposed, dispersed, and classified to produce nanosilicon composite nanoparticle powder.

[0145] The nanosilicon composite material contains more than 5 weight percent nanosilica powder, and the anode after mixing with artificial graphite is made up of 80 weight percent anode active material, 10 weight percent super P conductive material, and 10 weight percent PVDF adhesive. A coin-type battery with a diameter of 20 mm and a height of 3.2 mm was manufactured using the nanosilicon composite powder as the anode active material.

[0146] In Experimental Example 11, the organic solvent in the plasma reaction chamber is ethanol, aluminum sulfate, and yttrium nitrate, and the solid content of aluminum sulfate in the solvent is 0.05%, and the content of yttrium nitrate is 0.01%. Then, a pair of stainless steel electrodes is attached. The P-type silicon wafer is cut into a lattice shape with a thickness of 0.8 mm, a width of 1 mm, and a length of 100 mm to prepare a silicon rod. The resistance value of the P-type silicon ingot is 1 Ω. The nanosilicon composite is fabricated using a capacitor charged at 11 kV. The carbon layer composite of the nanosilicon composite is filtered through a steel mesh and centrifuged at 11000 rpm to obtain a nanosilicon particle slurry.

[0147] This slurry is subjected to high-temperature heat treatment at 1300°C for three hours in a nitrogen atmosphere, after which it is decomposed, dispersed, and classified to produce nanosilicon composite nanoparticle powder.

[0148] The nanosilicon composite material contains more than 5 weight percent nanosilica powder, and the anode after mixing with artificial graphite is made up of 80 weight percent anode active material, 10 weight percent super P conductive material, and 10 weight percent PVDF adhesive. A coin-type battery with a diameter of 20 mm and a height of 3.2 mm was manufactured using the nanosilicon composite powder as the anode active material.

[0149] As shown in Figures 12 and 13, which are SEM images of the anode active material prepared based on Experimental Example 11 in Figure 6, the synthesized nanosilicon powder can be observed from the SEM images of Experimental Example 11. In addition to the original silicon particles, the formation of nanometer silicon wires can also be confirmed.

[0150] In Experimental Example 12, the organic solvent in the plasma reaction chamber contains ethanol and aluminum nitrate. The solid content of aluminum nitrate in the solvent is 0.05%, and a pair of stainless steel electrodes is attached. A P-type silicon wafer is cut into a grid shape with a thickness of 0.8 mm, a width of 1 mm, and a length of 100 mm to prepare silicon rods. The resistance value of the P-type silicon ingot is 1 Ω. A nanosilicon composite is fabricated using a capacitor charged at 11 kV. The carbon layer composite of the nanosilicon composite is filtered through a steel mesh and centrifuged at 11000 rpm to obtain nanosilicon particle slurry.

[0151] This slurry is subjected to high-temperature heat treatment at 1300°C for three hours in a nitrogen atmosphere, after which it is decomposed, dispersed, and classified to produce nanosilicon composite nanoparticle powder.

[0152] The nanosilicon composite material contains more than 5 weight percent nanosilica powder, and the anode after mixing with artificial graphite has a positive electrode active material that accounts for 80% of the total weight of the anode, and is made of 10 weight percent Super P conductive material and 10 weight percent PVDF adhesive. A coin-type battery with a diameter of 20 mm and a height of 3.2 mm was manufactured using the nanosilicon composite powder as the positive electrode active material.

[0153] As shown in Figures 14 and 15, which are SEM images of the anode active material manufactured based on Experimental Example 12 in Figure 6, the synthesized nanosilicon powder can be observed from the SEM images of Experimental Example 12. The present powder was analyzed using Energy-dispersive X-ray spectroscopy (EDS) of the SEM and found to be composed of silicon material and confirmed to be generated by nanosilicon wires.

[0154] From the above experimental examples 1 to 12, the nanosilicon composite material produced after modifying the silicon powder has superior performance in terms of electrical conductivity, charge capacity, discharge capacity, initial discharge efficiency, and cycle efficiency after multiple charge and discharge, compared to the currently available commercially available silica powder (Comparative Example 1).

[0155] Compared with Comparative Example 2, the nanosilicon composite modified by doping not only has improved powder conductivity, but also the charge capacity of the pure silicon anode and the discharge capacity of the pure silicon anode are increased by at least 8% and 13%, respectively.

[0156] Figure 16 shows specific experimental data on the expansion characteristics of the experimental example of the present invention. Refer to the experimental data shown in Figure 16 to know the following: The nanosilicon composite material produced by modifying silicon powder has a further reduced expansion at the anode, and if nanosilicon wires are formed in the nanosilicon composite material, the expansion rate of the electrode plate can be further reduced.

[0157] It should be noted that a person skilled in the art may make various modifications to the matters specified in the claims, and that embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. Furthermore, new technical features can be formed by combining the technical features shown in each embodiment.

[0158] Furthermore, the numerical values ​​mentioned in the present invention do not mean that the present invention can be implemented only with those numerical values, and the numerical values ​​mentioned are merely examples. As can be understood by those having ordinary knowledge in the field, there are allowable errors in each numerical value and mixing ratio. As long as it does not have a significant effect on the intended results and functions of each experimental example, any numerical value close to the exemplified range is deemed to belong to the range shown in the present invention. [Explanation of symbols]

[0159] 10. Lithium secondary battery 11 Cathode 110 Cathode material layer 111 Cathode current collector 12 Diaphragm 13 Anode 130 Anode material layer 131 Anode current collector 200 Composite materials 210 Silicon particles 220 Ceramic Materials 230 Conductive Carbon M1 Anode active material M2 conductive material M3 Glue S110-S130, S210-S270 Flowchart of the manufacturing method of the anode active material

Claims

1. A positive electrode active material for a secondary battery comprising a composite material including silicon particles, a ceramic material, and conductive carbon, the ceramic material is formed on at least a portion of a surface of the silicon particles; the conductive carbon is formed on the ceramic material so as to cover the silicon particles and the ceramic material; The chemical formula of the ceramic material is MxSi12-(m+n)Al(m+n)OnN16-n, In the above chemical formula, M is any one of elements or compounds thereof selected from the group consisting of yttrium (Y), zirconium (Zr), rhodium (Rh), palladium (Pd), lithium (Li), magnesium (Mg), calcium (Ca), barium (Ba), cerium (Ce), neodymium (Nd), europium (Eu), and ytterbium (Yb); In the above chemical formula, x=0.01 to 0.5, m=0.1 to 2, and n=0.1 to 3.

2. The positive electrode active material for a secondary battery described in claim 1, characterized in that the composite material is produced by performing plasma treatment on a silicon material immersed in an organic solvent to obtain the ceramic material coating the silicon particles, and the organic solvent contains an alcohol compound, an aluminum compound and a flux.

3. 2. The positive electrode active material for a secondary battery according to claim 1, wherein the composite material is in a powder form and has a secondary particle diameter of 1 to 500 μm.

4. 2. The positive electrode active material for a secondary battery according to claim 1, wherein the primary particle diameter of the composite material is 5 nm or more and 1000 nm or less.

5. The positive electrode active material for a secondary battery according to claim 1 , wherein the silicon particles include at least one of spherical units and linear units.

6. 6. The positive electrode active material for a secondary battery according to claim 5, wherein the diameter of the spherical units is between 5 nm and 1000 nm, and the diameter of the linear units is between 2 nm and 40 nm.

7. 7. The positive electrode active material for secondary batteries according to claim 6, wherein the thickness of the ceramic material is between 0.1 nm and 3 nm.

8. 8. The positive electrode active material for a secondary battery according to claim 7, wherein the conductive carbon has a thickness of between 3 nm and 10 nm.

9. A cathode; A diaphragm; A lithium secondary battery comprising: the cathode and the anode are disposed on opposite sides of the diaphragm, the anode includes an anode active material, and the anode active material includes a composite material including silicon particles, a ceramic material, and conductive carbon; The chemical formula of the ceramic material is MxSi12-(m+n)Al(m+n)OnN16-n, In the above chemical formula, M is any one of elements or compounds thereof selected from the group consisting of yttrium (Y), zirconium (Zr), rhodium (Rh), palladium (Pd), lithium (Li), magnesium (Mg), calcium (Ca), barium (Ba), cerium (Ce), neodymium (Nd), europium (Eu), and ytterbium (Yb); In the above chemical formula, x=0.01 to 0.5, m=0.1 to 2, and n=0.1 to 3.

10. 10. The lithium secondary battery of claim 9, wherein the weight percentage of the positive electrode active material in the positive electrode is at least 70%.

11. Add an organic solvent to a reaction chamber, the reaction chamber being provided with a plurality of electrodes, and the organic solvent includes an alcohol compound, an aluminum compound, and a flux; placing a silicon material in the reaction chamber and contacting the organic solvent; applying a voltage to the plurality of electrodes to perform a plasma treatment to produce a composite material including silicon particles, a ceramic material, and conductive carbon; the organic solvent is heated during plasma treatment to produce the ceramic material that coats the surfaces of the silicon particles; The chemical formula of the ceramic material is MxSi12-(m+n)Al(m+n)OnN16-n, In the above chemical formula, M is any one of elements or compounds thereof selected from the group consisting of yttrium (Y), zirconium (Zr), rhodium (Rh), palladium (Pd), lithium (Li), magnesium (Mg), calcium (Ca), barium (Ba), cerium (Ce), neodymium (Nd), europium (Eu), and ytterbium (Yb); In the above chemical formula, x=0.01 to 0.5, m=0.1 to 2, and n=0.1 to 3.

12. 12. The method of claim 11, wherein the flux contains any one of the elements yttrium, zirconium, rhodium, palladium, lithium, magnesium, calcium, barium, cerium, neodymium, europium, and ytterbium or compounds thereof.

13. subjecting the composite material to a filtering process; The method for producing a positive electrode active material according to claim 11, characterized in that the composite material after filtration is subjected to a heat treatment.

14. 14. The method of claim 13, wherein the heat treatment comprises heating the composite material at a heating temperature of 900° C. to 1500° C. in an inert environment to produce the composite material in powder form.

15. 15. The method for producing a positive electrode active material according to claim 14, wherein the heating temperature is 1200° C. to 1500° C.

Citation Information

Patent Citations

  • Silicon-carbon negative electrode material, preparation method and application thereof, and prepared lithium ion battery

    CN111384378A

  • Silicon composite and its manufacturing method, and negative electrode material for nonaqueous electrolyte secondary battery

    JP2006019127A

  • NONAQUEOUS ELECTROLYTE SECONDARY BATTERY NEGATIVE ELECTRODE MATERIAL AND Si-O-Al COMPOSITE MANUFACTURING METHOD, AND NONAQUEOUS ELECTROLYTE SECONDARY BATTERY NEGATIVE ELECTRODE AND NONAQUEOUS ELECTROLYTE SECONDARY BATTERY

    JP2010055775A

  • Negative electrode material for non-aqueous electrolyte secondary battery, method of manufacturing the same, and lithium-ion secondary battery

    JP2011096455A

  • Method for producing silicon-based nanocomposite cathode active material for lithium secondary batteries and lithium secondary battery using the same

    JP2013546144A